PENGARUH KECERDASAN EMOSIONAL TERHADAP KOMUNIKASI INTERPERSONAL PESERTA DIDIK DI SMP N 12 PADANG - Agtriani Kurnia Putri; Imelda Usman; Mori Dianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of emotional intelligence on interpersonal communication of students at SMP Negeri 12 Padang. The background of this study is the emergence of various communication problems between students which are thought to be caused by a lack of emotional management. This study uses a quantitative approach with a simple linear regression method. The research sample consisted of 103 students determined by purposive sampling technique. The research instrument was a questionnaire. The results of the analysis show that (1) students' emotional intelligence is in the fairly high category, (2) students' interpersonal communication is in the fairly high category, and (3) there is an influence of emotional intelligence on students' interpersonal communication by 26%. It is recommended that students improve their emotional intelligence in building effective communication relationships.